UMP, FeMAC outline a collaboration to strengthen TVET programmes - Mimi Rabita, Abdul Wahit (2021)
KUALA LUMPUR, 25 November 2021 - The strategic collaboration between Universiti Malaysia Pahang (UMP) and the Federation of JPK Accredited Centers Malaysia (FeMAC) will provide opportunities for graduates of the Malaysian Vocational Diploma (DVM), Malaysian Skills Diploma (DKM), and Malaysian Advanced Skills Diploma (DLKM) to continue their studies in the Bachelor of Technology programme offered by this university.